Transforming New Ideas into Practice: An Activity Based Perspective on the Institutionalization of Practices - Reay, Trish; Chreim, Samia; Golden‐Biddle, Karen; Goodrick, Elizabeth; Williams, B. E. (Bernie); Casebeer, Ann; Pablo, Amy; Hinings, C. R. (Bob) (Journal of Management Studies, 2013)
We develop an activity‐focused process model of how new ideas can be transformed into front line practice by reviving attention to the importance of habitualization as a key component of institutionalization. In contrast to established models that explain how ideas diffuse or spread from one organization to another, we employ a micro‐level perspective to study the subsequent intra‐organizational processes through which these ideas are transformed into new workplace practices. We followed efforts to transform the organizationally accepted idea of ‘interdisciplinary teamwork’ into new everyday practices in four cases over a six year time period. We contribute to the literature by focusing on de‐habitualizing and re‐habitualizing behaviours that connect micro‐level actions with organizational level theorizing. Our model illuminates three phases that we propose are essential to creating and sustaining this connection: micro‐level theorizing, encouraging trying the new practices, and facilitating collective meaning‐making.